1994
DOI: 10.1002/jcp.1041590316
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle controlled histone H1, H3, and H4 genes share unusual arrangements of recognition motifs for HiNF‐D supporting a coordinate promoter binding mechanism

Abstract: Cell cycle and growth control of the DNA binding and transactivation functions of regulatory factors provides a direct mechanism by which cells may coordinate transcription of a multitude of genes in proliferating cells. The promoters of human DNA replication dependent histone H4, H3, and H1 genes interact with at least seven distinct proteins. One of these proteins is a proliferation-specific nuclear factor, HiNF-D, that interacts with a key cis-regulatory element (H4-Site II; 41 bp) present in H4 genes. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 70 publications
2
23
0
Order By: Relevance
“…We propose that p110 CDP/Cux plays a role in the establishment of at least part of the S-phase-specific transcription program and that CDP/Cux does not act alone in the regulation of S-phase-specific genes but rather functions in combinatorial fashion with other transcription factors. This mode of action would be entirely consistent with known features of the HiNF-D complex, which resides on the promoter of histone genes during S phase (4,5,30,(68)(69)(70)(71)(72). Moreover, this mechanism of action would explain why cells reach S phase faster in the presence of p110 CDP/Cux but are still able to proliferate in its absence, albeit more slowly.…”
Section: Discussionsupporting
confidence: 80%
“…We propose that p110 CDP/Cux plays a role in the establishment of at least part of the S-phase-specific transcription program and that CDP/Cux does not act alone in the regulation of S-phase-specific genes but rather functions in combinatorial fashion with other transcription factors. This mode of action would be entirely consistent with known features of the HiNF-D complex, which resides on the promoter of histone genes during S phase (4,5,30,(68)(69)(70)(71)(72). Moreover, this mechanism of action would explain why cells reach S phase faster in the presence of p110 CDP/Cux but are still able to proliferate in its absence, albeit more slowly.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, we envision that CDP/Cux p110 might contribute, perhaps as an architectural factor, to the formation of a larger complex or enhanceosome (22). This mode of action would be consistent with what we know of the HiNF-D complex, which includes CDP/Cux as well as a number of other proteins, and whose presence on the promoter of histone genes coincides with their induction in S phase (3,4,36,67,(70)(71)(72)(73).…”
Section: Discussionsupporting
confidence: 57%
“…The mechanism by which short isoforms of CUX1 function in transcriptional activation was not immediately apparent, since in the Gal4 DNA binding domain fusion assay two active repression domains were identified downstream of the Cut homeodomain, but no region of CUX1 was found to function as an activation domain (44). One clue, however, was suggested from the finding that CUX1 is the DNA binding subunit of the HiNF-D protein complex that regulates transcription of cell cycle-regulated histone genes (1,27,35,(74)(75)(76)(77). These results suggested that CUX1 could be part of larger nucleoprotein complexes that regulate transcription.…”
Section: Discussionmentioning
confidence: 99%
“…CUX1 was also reported to regulate the expression of cell cycle-regulated genes such as those encoding p21 WAF1 (7), histones H1, H2A, H2B, H3, and H4 (12,27,74,76), and DNA polymerase (Pol) ␣ (71). The full-length protein, p200 CUX1, interacts transiently with DNA and is expressed throughout the cell cycle (48).…”
mentioning
confidence: 99%